Development of Kampung Hulu Melaka : its mosque and the impact to the surrounding / Syed Alwi Alhabshi - Syed Alwi, Alhabshi (Faculty of Architecture,Planning and Surveying, 1981)
Kampong Hulu area and its influence on the Islamic expansion in Melaka has gone a long way hack since the time of parameswara as related by Munshi Abdullah, (a well known Malay figure). The significant of this area is due to its importance in religion that is Islam which spreads throughout Melaka eventually. Kampong Hulu in the olden times as related by the bilal of the mosque was known as the •Seraxnbi of Melaka1 meaning the area is the seat, for seeking Islamic religion. People from the exterior and the inland areas converge to this area to seek knowledge in Islamic religion. Due to this importance I chose thin area £or my research in the mosque towards the social surrounding and its impact onthe planning of the layout.